Comparison of the Use of Animated and Non-Animated Video Media on Students' Cognitive Performance on Health Materials - Fanhas Fanhas; Ranu Baskora Aji Putra (Universitas Negeri Semarang, 2026)
Video media serves as a powerful instructional tool, effectively presenting materials through an integration of visual and auditory elements that enhance student engagement and retention. This study aims to assess the impact of animated versus non-animated video media on the cognitive learning outcomes of Grade XI students at MAN 1 Bekasi. Employing a quasi-experimental design utilizing a Two Groups Pretest–Posttest approach, the research conducted cluster sampling across eight classes. Data were gathered through a validated multiple-choice. The statistical analysis demonstrated that both animated (Z = -7.711, p < 0.05) and non-animated (Z = -9.813, p < 0.05) videos significantly improved student learning outcomes. However, the Mann-Whitney U test (U = 33525.500, p = 0.763 > 0.05) indicated no significant difference in effectiveness between the two media types. Consequently, both animated and non-animated videos are equally effective in enhancing cognitive achievement. This finding suggests that educators have the flexibility to utilize either format to achieve comparable pedagogical results in physical education